Pengaruh Parameter EDM Terhadap Ketirusan Pada Pembuatan Lubang Tembus - Triyono, Triyono (MESIN, 2007)
Tapering Effect of parameter EDM in hole making process. EDM is one of nontraditional machining. There are some advantages of this process for instance suitable for machininghigh strength temperature resistance material, accurate and beableto make complex geometricfeature.How ever, there aresomeweaknesses: lowrateof material removal, tapering, highcostandenvironmentproblem. This paper willexamine the influence ofcutting parameter toward tapering using EDMinholemaking process. The parameters are electric current (from 15A, 20 A, 30 A, 45 A and60 Ampere) andthe dutyfactor (from 30%, 40%, 50%, 60%, 70% and90%). Experiment has been donewith SKD 11 aswork piece material, Cufor electrode and kerosenefor dielectricfluid. Taper can bemeasured by usingTriobor which has I micrometer resolution. Conclusion of the experimental showed that variation ofelectric current gives different taper values.